Aux armes, antivax! Uma análise da estruturação comunicacional do coletivo Lyon Pour La Liberté - Ruedell, Eduardo (2023)
This dissertation investigates the communicational structuring of the French social movement Lyon Pour la Liberté from what the collective "says" through its communicational actions, and by what is "said'' of the collective by other social actors and subjects articulated around the anti-vaccine and anti-health-care pass agenda in France between October 2021 and September 2022. For the investigation to be possible, two important delimitations were carried out: first, we chose to investigate the actions of the collective in its two public groups on Telegram, and in social media networks (CARLÓN, 2020) and websites of information vehicles when their discourses were taken up in the Telegram groups of the self-titled Collective; then, three distinct communicational episodes were selected, represented by the dates in which they took place (27/12/2021; 24/01/2022; and 17/05/2022) and which served as a basis for data collection from these devices. The method privileged the evidential paradigm (Ginzburg, 1980; Braga, 2008) as a "guide" for the investigation, and the analytic device for hypermedia circulation (Carlón, 2018, 2020, 2021). The epistemological axis is constituted by a panorama that contemplates mediatization (Verón, 1993, 2004, 2013, 2014; Tudor & Bratosin, 2021; Hepp & Couldry, 2016), circulation of meanings (Boutaud & Verón, 2007; Verón, 2013; Carlón, 2018, 2020, 2021; Fausto Neto, 2018), and social movements (Jamison & Eyerman, 1990; Montevechi, 2021; Mattoni & Treré, 2014). From this theoretical-methodological construction, it is possible to infer that Lyon Pour la Liberté focuses its communicational structure around its Telegram groups, even if it has pages on diverse social media networks. Moreover, the institutionalization of one of its leaders was observed, as well as the restructuring of the collective, which as of September 2022 was renamed En Avant!. It is also worth highlighting the formation of circuits from circulation (BRAGA, 2012, 2017), and the existence of a larger and more complex network of new social collectives and actors articulated around the creation and dissemination of anti-vaccine discourses and false information about Covid-19.